Influence of the First Wave of the COVID-19 Pandemic on Cancer Care in a German Comprehensive Cancer Center - Johanna Kirchberg; Johanna Kirchberg; Anke Rentsch; Anna Klimova; Vasyl Vovk; Vasyl Vovk; Sebastian Hempel; Sebastian Hempel; Gunnar Folprecht; Mechthild Krause; Mechthild Krause; Mechthild Krause; et al. (Frontiers Media S.A., 2021)
Introduction: During the first wave of the COVID-19 pandemic in 2020, the German government implemented legal restrictions to avoid the overloading of intensive care units by patients with COVID-19. The influence of these effects on diagnosis and treatment of cancer in Germany is largely unknown.Methods: To evaluate the effect of the first wave of the COVID-19 pandemic on tumor board presentations in a high-volume tertiary referral center (the German Comprehensive Cancer Center NCT/UCC Dresden), we compared the number of presentations of gastrointestinal tumors stratified by tumor entity, tumor stage, and treatment intention during the pandemic to the respective data from previous years.Results: The number of presentations decreased by 3.2% (95% CI −8.8, 2.7) during the COVID year 2020 compared with the pre-COVID year 2019. During the first shutdown, March-May 2020, the total number of presentations was 9.4% (−18.7, 1) less than during March-May 2019. This decrease was significant for curable cases of esophageal cancer [N = 37, 25.5% (−41.8, −4.4)] and colon cancer [N = 36, 17.5% (−32.6, 1.1)] as well as for all cases of biliary tract cancer [N = 26, 50% (−69.9, −15)] during the first shutdown from March 2020 to May 2020.Conclusion: The impact of the COVID-19 pandemic on the presentation of oncological patients in a CCC in Germany was considerable and should be taken into account when making decisions regarding future pandemics.